Extraction and Characterization of Collagen from Cattle Horns for Potential Wound Healing - Halson, Yeriko; Haule, Liberato; Nambela, Lutamyo; Komba, Nathan; Lyantagaye, Sylvester (Tanzania Journal of Engineering and Technology, 2025)
The need for bandages and gauze for wound dressing and healing is inevitable due to the high increase in accidents. Most of the material used for the production of bandages and gauzes for wound healing are from non-renewable synthetic material. The sustainability of non renewable resources is at jeopardy due to the health and associated environmental impact. Consequently, the use of naturally occurring and biodegradable material is a promising solution to the sustainability challenges of synthetic material. In this paper, the extraction of collagen films from cattle horns for potential wound healing is reported. Collagen was extracted from cattle horns by acid soluble method. The maximum yield of collagen was 12% (on dry weight basis). The physicochemical characterization was carried out to confirm the purity and structural integrity of the extracted collagen. Based on the SDS-PAGE analysis, the estimated molecular weight of the α chain and β chain were approximately 135 kDa and 245 kDa respectively. UV/Vis absorption peak at 220 nm indicated that the collagen produced was type I collagen. FTIR spectra showed regions of amides A, B, I, II, and III were 3424, 2932, 1640, 1564, and 1230 cm-1 respectively. The results of this study indicate that, cattle could be used as an alternative source for collagen extraction. However, further study is required to optimize the conditions for collagen extraction from cattle horns including acid concentration,pH, time and temperature in order to increase yield.